DAMPAK PENURUNAN SUBSIDI BAHAN BAKAR MINYAK: ANALISIS SISTEM NERACA SOSIAL EKONOMI INDONESIA - Kurniawati, Lestari (Polytechnic of State Finance STAN, 2017)
Fuel subsidies create a heavy burden for state budget, ineffective as poor social protection, and creating environmental problem. This study using Social Accounting Matrix to analyze the impact of fuel subsidies removal and cash transfer policies to Indonesian economy, household income distribution, and the level of CO2 emission. As the results, fuel subsidy removal with cash transfer compensation, in short term, it will give better effect than non-cash transfer compensation. Another finding was that subsidy removal with sector targeted policy gives better impact for the sector which had direct relation to the fuel subsidy sector than the sector indirect related. Furthermore, diesel subsidy removal gives better affects than gasoline and kerosene subsidy removal.